Compact Triple-Band Antenna Employing Simplified MTLs for Wireless Applications - Zhangjing Wang; Yang Peng; Yahua Ran (International Journal of Antennas and Propagation)
A compact triple-band asymmetric coplanar waveguide- (ACPW-) fed antenna based on simplified metamaterial transmission lines (SMTLs) is proposed in this paper. The antenna consists of two SMTL unit cells of the same dimension. Three operating bands, which cover UMTS in the 1.76 GHz band and WLAN in the 5.2 GHz and 5.8 GHz, are achieved when the zeroth-order and first-positive-order modes appear. The characteristics of the proposed transmission line metamaterial structure are studied in detail by circuit analysis and dispersion analysis. The working mechanism and radiation performances of the antenna are examined and illustrated at the three operating bands, respectively. A prototype designed on FR4 substrate with dielectric constant 4.3 occupies an overall size of 12.55 × 22.7 × 1.6 mm3 and is constructed and successfully measured.